Evaluating crop yield and water productivity of onion and potato through the use of wetting front detectors by water user associations in Koga irrigation Scheme, Ethiopia - Taye, B. M.; Schmitter, Petra S.; Tilahun, Seifu A. (2017)
Whilst irrigation schemes and technologies are extensively promoted in Africa, proper water management guidance for farmers is often lacking. Improper on-farm irrigation management practices lead to poor water distribution, non-uniform crop growth, and disputes in irrigation schemes due to unequal water allocation. Hence, the objective of the study was evaluating crop yield and water productivity of onion and potato through the use of wetting front detectors by water user association. In Koga irrigation scheme, there are 11 night storage, which irrigate 12 blocks (7000 ha). From those three blocks (Tagel, Adibera and Chihona blocks) were selected. From each block two water users association (WUA) have been selected and training on how to use the Wetting front detector (WFD) was given: one WUA grew onion while another one cultivated potato. For onion 2.04 ha of land were managed by 9 WFD and 0.82ha were managed by farmer’s own irrigation system. For potato 1.68 ha of land were managed by 10 WFD and 0. 42 ha of land were managed by farmers own irrigation system. In this study a total of 43 farmers irrigated using WFD while 13 farmers were irrigating based on their traditional knowledge. During installation the furrow length for onion was 5m and for potato 20m. The WFD was placed at ¾ of the furrow length from the entrance of the furrow. The shallow detector installed at 1/3 of the root zone (20 cm in this case) and the deep detector installed at 2/3 of the root zone (40 cm). Potato fields that were irrigated based on WFD response received on average 43% less water compared to control fields (i.e. 431mm instead of 753mm) (p<0.05). This resulted in a significant yield increase of 6 % (p<0.05) in the WFD plots. Similarly, for onion a reduction in irrigation depth of 25% was obtained when farmers were guided by WFD (i.e. 504 mm instead of 676mm (p<0.05). While yield increased in the WFD fields by 4%, this was not significant. At scheme level, if all fields were onion guided by WFD, 1509 ha additional could be irrigated. Similarly if all fields were potato guided by WFD, additional land to be irrigated could be 2966 ha. This study has shown that available water in dams can irrigate more land by using on farm water management technologies.